2012
DOI: 10.1002/kin.20611
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of acrylamide radical polymerization initiated by the horseradish peroxidase–mediated system

Abstract: The polymerization kinetics of acrylamide (AAM) in water initiated by a ternary enzymatic system of horseradish peroxidase (HRP)/H2O2/acetylacetone (ACAC) was investigated. Conversion–time plots were obtained by dilatometry under different conditions of reaction temperatures and initial concentrations of HRP, ACAC, H2O2, and AAM. The results showed that the effect of the initial concentration of ACAC on the inhibition period was significant. The inhibition period decreases with increasing the initial concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…39 The utility of HRP for the initiation of polymerization reactions is well-documented and has been used to synthesize polymers through the oxidative polymerization of phenols 40 and the free-radical, chain-growth polymerization of acrylamides 41 and (meth)acrylates. 42 For example, poly(methyl methacrylate) (PMMA) was synthesized from a formulation of methyl methacrylate, HRP, hydrogen peroxide, and acetylacetone as a substrate for HRP-mediated oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…39 The utility of HRP for the initiation of polymerization reactions is well-documented and has been used to synthesize polymers through the oxidative polymerization of phenols 40 and the free-radical, chain-growth polymerization of acrylamides 41 and (meth)acrylates. 42 For example, poly(methyl methacrylate) (PMMA) was synthesized from a formulation of methyl methacrylate, HRP, hydrogen peroxide, and acetylacetone as a substrate for HRP-mediated oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…An in-depth exploration of the polymerization of acrylamide by HRP, hydrogen peroxide, and acetylacetone was performed by Wen and coworkers to provide insight into some of the questions raised by earlier work [ 34 ]. Regarding the lengthy inhibition periods observed by Lalot [ 31 ], Wen found that the inhibition period prior to polymerization was caused by oxygen inhibition.…”
Section: Enzyme-mediated Polymerization Reactionsmentioning
confidence: 99%
“…This inhibition time could be reduced or eliminated by increasing the concentration of acetylacetone, to as high as 0.13 M, as this led to an increase in the radical generation rate; as these radicals reacted with and consumed oxygen, propagation reactions successfully competed with the inhibition reactions allowing the polymerization to proceed once the oxygen concentration was sufficiently low. Owing to the reduced inhibitory period, reactions times were significantly shorter than those observed by Lalot; however, the synthesized poly(acrylamide) batches were similar to those described by Lalot, having M n s of 200 to 630 kg/mol and dispersities ( Đ ), a measure of the molecular weight distribution width, of 2.0 to 3.0, with yields of 72% to 97% [ 34 ].…”
Section: Enzyme-mediated Polymerization Reactionsmentioning
confidence: 99%
“…The initiation is thus totally dependent on the enzymatic activity. Indeed, hydrogen peroxide appears to have three contributions in the initiating system: (i) it is one of the two substrates of HRP (the other being ACAC) and leads to the formation of compound I; (ii) it is an inhibitor of HRP since compound III is formed in the presence of an excess of H 2 O 2 , and leads to an irreversible inactivation of HRP; this can be inter pretend as a loss of a part of the HRP initially introduced; (iii) it consumes a part of the ACAC initially added by the formation of P-IV (cyclic peroxide decomposition) [9][10][11]. The reaction for graft polymerization of degraded starch with CA-HPA is showed in Fig.…”
Section: Mechanism Of Enzyme Catalyzed Copolymerizationmentioning
confidence: 99%